2001
DOI: 10.5271/sjweh.597
|View full text |Cite
|
Sign up to set email alerts
|

Cohort cancer incidence among pulp and paper mill workers in British Columbia

Abstract: cancer incidence among pulp and paper mill workers in British Columbia. Scand J Work Environ Health 2001;27(2):113-119.Objectives A study was conducted to investigate cancer risks in a cohort of pulp and paper workers. Methods All male workers with ≥1 years of employment in 14 pulp and paper mills in 1950-1992 were studied. Standardized incidence ratios (SIR) were used to compare the cancer incidence of the cohort with that of the Canadian male population. Record linkage with the National Cancer Registry was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 25 publications
0
12
1
Order By: Relevance
“…Previously reported risk excesses in Sweden were of gliomas, which are usually fatal, thus any signiWcant increase in them should be detectable in a mortality study of this kind. Many other studies have found increased risks for lung cancer among pulp and paper mill workers, with asbestos, sulfur dioxide as well as sulWte pulping among the suggested causal exposures (Torén et al 1996b;Band et al 1997Band et al , 2001Henneberger and Lax 1998;Langseth and Andersen 2000;Carel et al 2002;Lee et al 2002). One study also found mill workers exposed to organochlorine compounds to have an increased risk for lung cancer (Jäppinen and Pukkala 1991), but IARC analyses of organochlorine compounds among pulp and paper mill workers could not conWrm these Wndings (McLean et al 2006).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Previously reported risk excesses in Sweden were of gliomas, which are usually fatal, thus any signiWcant increase in them should be detectable in a mortality study of this kind. Many other studies have found increased risks for lung cancer among pulp and paper mill workers, with asbestos, sulfur dioxide as well as sulWte pulping among the suggested causal exposures (Torén et al 1996b;Band et al 1997Band et al , 2001Henneberger and Lax 1998;Langseth and Andersen 2000;Carel et al 2002;Lee et al 2002). One study also found mill workers exposed to organochlorine compounds to have an increased risk for lung cancer (Jäppinen and Pukkala 1991), but IARC analyses of organochlorine compounds among pulp and paper mill workers could not conWrm these Wndings (McLean et al 2006).…”
Section: Discussionmentioning
confidence: 87%
“…However, the same could not be conWrmed in this cohort; if there was any increase, it was among sulfate pulping male workers during 1952-1971. In the cohort analyses we Wnd some increased mortalities of cancer that could be due to chance which, however, needs further discussion. Besides smoking, few risk factors are known for pancreatic cancer, although a few other reports of increases in pancreatic cancers among pulp and paper mill cohort studies from several departments have been published (Band et al 2001;Wild et al 1998). The female oYce workers showed increased mortality from pancreatic cancer but no increases in lung cancer mortality, suggesting that they did not smoke any more than the general population, although the group studied was too small to draw Wrm conclusions.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Some early studies (Lee and Fraumeni 1969;Rencher et al 1977) in SO 2 -exposed workers showed an increased mortality from lung cancer, but in those studies exposure to SO 2 occurred together with exposure to known or suspected carcinogens such as arsenic. Previous studies have reported an increased mortality from lung cancer among workers employed in the pulp and paper industry and, in particular, in sulfite pulp manufacture and maintenance (Band et al 2001;Langseth and Andersen 2000;Szadkowska-Stanczyk and Szymczak 2001;Toren et al 1991). It was suggested that asbestos, dust, or chlorinated compounds could be among the agents responsible for the increased lung cancer mortality, but no formal attempt was made in these studies to assess exposure to specific agents.…”
mentioning
confidence: 88%
“…A pulp and paper mill cohort in Canada showed increased mortality for brain tumors among sulfite mill workers (table 4) (4). When the incidence in the same cohort was studied, but with a shorter follow-up time, the increase was no longer significant (table 3) (12). In an internal comparison in a large cohort mortality study in the United States, an increased risk was observed among workers in semi-chemical and soda pulp processing (relative risk 2.3, 95% CI 1.4-3.9) as compared with other pulp and paper mill workers (5).…”
Section: Discussionmentioning
confidence: 98%